PERAN GREEN SATISFACTION MEMEDIASI HUBUNGAN GREEN BRAND IMAGE TERHADAP GREEN BRAND EQUITY - Pratama, I Putu Dipa Wahyu; Suryani, Alit (E-Jurnal Manajemen, 2017)
This study aims to prove a role in mediating the relationship green brand image and green satisfaction of green brand equity. The sampling method using a non-porbability sampling through accidental sampling and purposive sampling with a sample size of 100 respondents. Data was collected by questionnaire directly spread in the city of Denpasar. The data analysis technique used is Path Analysis (Path Analysis) and Test Sobel. The results showed that green satisfaction can provide mediation effect on brand image teradap green green brand equity. These results prove that green satisfaction has a role in bridging the influence of variable green brand image of green brand equity. So it is important for mamajemen companies that are implementing the concept of green marketing in their marketing strategies to pay attention to the variables green brand image, green satisfaction, and green brand equity in marketing their products.